Teaching Sight Impaired IT Students - Murray, Iain; Armstrong, Helen (2005)
This paper describes a research project to convert Cisco network administration e- learning education materials to a format that can be accessed and undertaken by sight impaired students. The changing nature of educational materials and the associated problems faced by vision impaired students are discussed. A description of both the high-tech and low-tech solutions applied to this unique teaching environment is presented. Results so far are reported together with a discussion of future plans for the project.